The Use of Pozzolanic Material for Improving Quality of Strontium Liquid Waste Cementation in Saline Environment during Nuclear Waste Immobilization Process - Muhammad Yusuf; Hayu Tyas Utami; Tri Sulistiyo Hari Nugroho; Susetyo Hario Putero (Bandar Lampung University (UBL), 2013)
This research was conducted to study the use of artificial pozzolanic material (portlandpozzolana cement or PPC) and natural pozzolanic material (fly ash) to improve quality of strontium liquid waste cementation in saline environment during nuclear waste immobilization process.The portland cement was mixed with 10 v/0 strontium liquid waste (water containing 65 ppm Sr(II)), 0.3 water-cement ratios (w/c), 20 v/0 fly ash, -40 mesh to -60 mesh sand. Similar process was performed using commercial portlandpozzolana cement (PPC). Compressive strength test after cured the block cements for 28 days was performed using pressing machine. To study leaching rate test, 10 ml contaminated saline water was sampled from immersion of cement block with 1 liter saline water for 21 days. Hitachi Zeeman 8000 Atomic Absorption Spectrophotometer was used for analyzing leaching rate test.All cement blocks showed the results above than 2.5 N/mm2 of IAEA standard during strength test. The fly ash showed 103-105% higher strength test than commercial PPC in all grain size. But the fly ash showed 4-5% less durable during leaching rate than commercial PPC during 21 days immersion. All the cement blocks showed the results above than IAEA standard during leaching rate test.The addition of natural pozzolanic material (fly ash) could improve the strength of strontium liquid waste cementation. In other hand, the artificial pozzolanic material could improve the durability from leaching rate of strontium liquid waste cementation